Modelagem e acionamento de uma máquina de indução de nove fases baseado em modulação espacial vetorial - SVPWM - Silva, Ivan da (2015)
The interest for the study of multiphase (more than three phases) machines and variable speed drives has substantially increased in the last two decades. The advantages presented by the multiphase systems compared to their three-phase counterparts have being the the main effort to increase researches all over the world. Reduction in torque oscillation, lower current ratings, high drive reliability, better fault tolerance and harmonic content reduction in the DC bus are some of these advantages. The additional degrees of freedom due to extra phases make multiphase systems very flexible when it comes to control systems and modulation strategies. Although three-phase systems are predominant in industrial applications, the use of multiphase machines and drives has increased in very specific areas such as locomotive traction, electric ship propulsion, aerospace industry (more electric aircraft), electric and hybrid vehicles and industrial high power systems. Due to high coupling degree between electric variables in multiphase systems, modeling of multiphase machines has been and still is a challenge task in research centers. In this present work, analitic modeling of symmetric and asymmetric nine-phase machines using natural variables and space vector decomposition are presented. The principles used in the study are the same used for three-phase systems. However, multiphase systems are analised in multiple d-q planes. PWM modulation strategies based on space vectors theory (SVPWM) for a voltage source inverter (VSI) are presented. The multiphase drive system presented works in the linear operation region with sinusoidal voltage generation. Results for both machines and drive modeled are verified by simulation programs developed in C programming language an Matlab.